Cytotoxicity of crystals involves RIPK3-MLKL-mediated necroptosis - Shrikant R. Mulay (Nature Portfolio, 2016)
Kidney stone disease is caused by accumulation of oxalate crystals, which trigger tissue injury, inflammation and cell death. Mulay et al. show that crystals induce cell death in the kidney through necroptosis, and propose that this pathway may be a target for the treatment of crystal-induced disease.